Garcinia spp. extract incorporated icing medium as a natural preservative for shelf life enhancement of chilled Indian mackerel (Rastrelliger kanagurta). (November 2020) - Apang, Toni; Xavier, K.A. Martin; Lekshmi, Manjusha; Kannuchamy, Nagalakshmi; Layana, Porayil; Balange, Amjad K.
Abstract: The present study investigates the use of a novel icing medium containing aqueous extract of two varieties of Garcinia fruit rinds, the culinary spices exhibiting antioxidant and antimicrobial activities, for the preservation of fish during chilled storage. Aqueous extracts of Garcinia indica and Garcinia cambogia were prepared and its phenolic content, antioxidant activities and antimicrobial properties were studied. Four icing media were prepared with 500 mg/L and 750 mg/L concentrations for each varieties of Garcinia extract. Conventional ice made of potable water was used as the control. The chilled fish was evaluated for the changes in pH, volatile basic compounds, oxidative parameters and total viable counts and the results were compared with those of sensory analyses. Mackerel stored in ice, prepared with different concentrations of garcinia extracts significantly reduced the values of trimethyl amine, total volatile basic nitrogen, peroxide value, thiobarbituric acid reactive substances and total viable counts compared to conventional icing. The shelf life of fish stored in ice as indicated by the results of sensory evaluation was observed to be 15 days, 21 days and 24 days under conventional icing system, ice containing Garcinia indica extract and ice containing Garcinia cambogia extract respectively. Highlights: Garcinia fruit rind extract containing ice was evaluated for improving fish quality. Total phenolics, antioxidants activities, microbial activity of aqueous extracts studied. Improved oxidative stability, reduced microbial load and extension of shelf life observed. Garcinia cambogia extracts containing Icing medium showing the better performance.